Analisis Kelembagaan Kelompok Usaha Bersama (KUBE) Fakir Miskin di Kabupaten Sumedang - Supiadi, Epi; Marjuki, Marjuki; Rosilawati, Rosilawati (Politeknik Kesejahteraan Sosial Bandung, 2024)
The institutional aspect of Joint Business Groups (KUBE) is very important in empowering the poor. This article discusses some of the research results of the KUBE for the Poor in Sumedang Regency, which used descriptive statistical methods with quantitative and qualitative approaches, with a purposive sampling technique producing a main sample of 52 respondents and a supporting sample of 33 informants from KUBE members, facilitators, assistants and officials. organizer of the KUBE FM Program. The research results show that the institutional aspect is in the medium to high category, where there are 25% of KUBE FM whose management and members are incomplete, 46.15% of KUBE FM do not have letterhead, 11.54% of KUBE FM do not have financial books, 3.85 % do not have recording and reporting, 25% do not have written and unwritten rules.The research conclusion shows the need for reorganization efforts, improving administration and group norms in at least 29% of KUBE FM